Coating process for preparing light-proof low-medium low-Tg polyimide film
Through secondary coating process and heat treatment plasma treatment, combined with the addition of PVA, the high dielectric constant and high temperature pressing problems of polyimide film are solved, and the opaque film with low dielectric constant and low Tg is achieved. in high-frequency electronic products.
Patent Information
- Application Number
- CN202411044387.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2025-01-07
AI Technical Summary
The existing polyimide film lacks light-shielding effect, has too high dielectric constant, and has high energy consumption during high-temperature pressing, which limits its application in high-frequency electronic products.
The secondary coating process and specific heat treatment and plasma treatment methods are used to reduce the dielectric constant and glass transition temperature (Tg) of the polyimide film, and PVA is added to the coating process to form an opaque low dielectric low Tg Polyimide film.
It realizes the reduction of the dielectric constant and Tg of the film, enhances the light shading effect, reduces the need for high-temperature pressing, and improves the high-frequency performance and stability of the film.
Smart Images

Figure SMS_4 
Figure SMS_5 
Figure SMS_6
Abstract
Description
Technical Field
[0001] The invention provides a coating process for preparing a light-proof low-dielectric low-Tg polyimide film, and relates to the technical field of special film material preparation. Background Art
[0002] Polyimide (PI) is a high-performance polymer containing imide groups (-CO-NH-CO-). It is widely used in aerospace, microelectronics, liquid crystal display, photovoltaic industry and other fields due to its excellent high temperature resistance, excellent mechanical properties, electrical insulation properties and chemical stability. Polyimide film is an important application form of polyimide materials, with important application value and research significance.
[0003] The coating process is a method of coating liquid polyamic acid or its solution on the surface of a substrate to form a polyimide film through subsequent treatment. The coating process has become one of the main methods for preparing polyimide films due to its advantages of simple operation, low equipment cost, easy control of film thickness and large-area production.
[0004] With the advancement of technology, the coating process has gradually developed towards simplification and efficiency, including automation of equipment and simplification of process flow. Typical coating methods include: Spin coating: dripping the solution onto a high-speed rotating substrate, and evenly distributing the solution to form a thin film through centrifugal force. Blade coating: using a blade to evenly coat the solution on the substrate, and controlling the film thickness by adjusting the distance between the blade and the substrate. Spray coating: spraying the solution onto the surface of the substrate through a nozzle to form a uniform film. Dip coating: immersing the substrate in the solution and then slowly pulling it out so that the solution evenly covers the surface of the substrate. Although the simplification of the coating process has improved production efficiency and reduced production costs, it has also brought some problems: Film thickness uniformity problem: simplified coating processes are prone to uneven film thickness when coating a large area, affecting the performance of the film. Solvent residue: in the process of rapid coating, incomplete evaporation of the solvent will cause residual solvent in the film, affecting the performance and stability of the film. Defect control: simplified coating processes have challenges in defect control, such as the appearance of defects such as bubbles and pinholes, which will affect the quality of the film.
[0005] Lack of light-shielding effect: Existing polyimide films generally do not have a light-shielding effect. When the mobile phone LED light is attached to the surface of the film for testing, if the light can penetrate the film and form a light spot, it means that its light-shielding performance is unqualified. This defect may cause product performance degradation or even functional failure in electronic products that require strict light control, such as mobile phone screens and photoelectric sensors. Therefore, it is particularly important to develop a polyimide film with light-shielding performance.
[0006] Dielectric constant is too high: The dielectric constant of polyimide film on the market is usually greater than 3.2. In high-frequency signal transmission, a too high dielectric constant will cause the signal to attenuate faster and reduce transmission efficiency. This is an issue that cannot be ignored for electronic products with 5G and higher frequencies. 5G technology has extremely high requirements for the high-frequency performance of materials. Therefore, reducing the dielectric constant of polyimide film and improving its high-frequency performance are the key to meeting the needs of the new generation of electronic products.
[0007] Limitations of high-temperature lamination: TPI film must be hot-melt-laminated (lamination temperature > 320°C) to heat-melt the surface T layer when in use. This not only increases energy consumption during the production process, but may also cause thermal damage to the material itself and other electronic components. In addition, high-temperature lamination also limits the use of TPI in certain temperature-sensitive application scenarios.
[0008] In view of the above problems, it is particularly important to develop a TBPI film with low dielectric constant, low TG (suitable for temperature and low pressure bonding) and light-shielding effect. However, the solutions currently adopted by researchers are generally in the modification of polyimide and film structure or formulation, and no improvement in coating method has been reported. Summary of the invention
[0009] In order to solve the above problems, the present invention is characterized in that starting from the coating method, the effect of reducing the dielectric constant of polyimide and reducing TG is achieved. The specific scheme is as follows:
[0010] A coating process for preparing a light-tight low-dielectric low-Tg polyimide film comprises the following steps:
[0011] (1) spraying the polyimide layer slurry on the surface of the polyimide film and pre-drying it;
[0012] (2) adding PVA to the polyimide layer slurry, stirring evenly and spraying it on the surface of the pre-dried coating for secondary pre-drying;
[0013] (3) heat treating the obtained film;
[0014] (4) The surface of the heat-treated film is subjected to plasma treatment to obtain an opaque, low-dielectric, low-Tg polyimide film.
[0015] Preferably, the pre-drying in step (1) comprises pre-drying at 90-95° C. for 30-40 min.
[0016] Preferably, the film thickness obtained by spraying in step (1) is 30-50% of the total spraying thickness.
[0017] Preferably, the amount of PVA added in step (2) is 3-5wt% of the slurry.
[0018] Preferably, the secondary pre-drying in step (2) comprises pre-drying at 80-85° C. for 30-40 min.
[0019] Preferably, the total thickness of the film obtained by spraying in step (1) and step (2) is 20-50 μm.
[0020] Preferably, the heat treatment in step (3) includes a first heat treatment and a second heat treatment, wherein the first heat treatment includes: heating to 150-180°C at 10-15°C / min and maintaining for 1-1.5h.
[0021] Preferably, in the heat treatment of step (3), the second heat treatment comprises: continuing to increase the temperature to 300-330°C at 20-30°C / min and maintaining for 2-2.5h.
[0022] Preferably, the plasma treatment in step (4) uses oxygen plasma equipment with a power setting of 90-100 W, an oxygen flow rate of 80-100 sccm, and a time of 20-30 min.
[0023] Preferably, the polyimide layer slurry includes: soluble polyimide liquid, high temperature resistant epoxy modified silicone resin, ion capture agent, antioxidant, curing agent, graphene, aluminum hydroxide, fluorine-containing resin, acid anhydride polymer material, diphenyl anhydride diamine, matte powder, diluent, and also includes silicon dioxide or zirconium oxide.
[0024] Preferably, the components in the polyimide layer slurry include, by mass: 30-120 parts of soluble polyimide liquid, 10-35 parts of high temperature resistant epoxy modified silicone resin, 0.3-1 parts of ion capture agent, 0.1-1 parts of antioxidant, 10-15 parts of curing agent, 10-15 parts of graphene, 15-35 parts of aluminum hydroxide, 10-35 parts of fluorine-containing resin, 10-35 parts of acid anhydride polymer material, 5-15 parts of diphenyl anhydride diamine, 5-15 parts of matte powder, diluent as needed, and also includes 10-35 parts of silicon dioxide or zirconium oxide.
[0025] Preferably, the components in the polyimide layer slurry are calculated by weight, wherein the mass ratio of the high temperature resistant epoxy modified silicone resin to the fluorine-containing resin is 10:10 or 35:15.
[0026] Preferably, the method for preparing the polyimide layer slurry comprises:
[0027] S1, dissolving the fluorine-containing resin and the epoxy-modified silicone resin in a diluent to prepare solutions of the fluorine-containing resin and the epoxy-modified silicone resin, respectively, stirring and dissolving them, mixing the two resin solutions, and transferring them to a reaction kettle after ultrasonic treatment, and mechanically stirring;
[0028] S2, subjecting matte powder and aluminum hydroxide to ultrasonic dispersion in a diluent, and adding soluble polyimide liquid to premix;
[0029] S3, adding the mixture obtained in S1 and S2 into a reaction kettle in a required proportion, adding an ion capture agent, an antioxidant, graphene, anhydride polymer material, diphenyl anhydride diamine, a curing agent and silicon dioxide or zirconium oxide, and mixing to obtain a polyimide layer slurry.
[0030] Preferably, the concentrations of the solutions of the fluorine-containing resin and epoxy-modified silicone resin in S1 are controlled at 10-20 wt %, respectively.
[0031] Preferably, the stirring and dissolving in S1 is carried out by stirring at room temperature for 2-3 hours using a magnetic stirrer to ensure that the resin is completely dissolved.
[0032] Preferably, the mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in the mixed solution in S1 is 10:10 or 35:15.
[0033] Preferably, the ultrasonic treatment described in S1 has an ultrasonic power of 100-200 W, a frequency of 20-40 kHz, and a treatment time of 30-60 min.
[0034] Preferably, the mechanical stirring speed in S1 is 300-500 rpm, and the stirring time is 4-6 h at room temperature.
[0035] Preferably, in the ultrasonic dispersion in S2, the ultrasonic power is 100-200 W, the frequency is 20-40 kHz, and the time is 30-45 min.
[0036] Preferably, the premixing in S2 is stirred at room temperature for 2-3 h using a magnetic stirrer.
[0037] Preferably, the mixing in S3 is carried out by stirring at room temperature for 4-5 hours at a rotation speed of 300-500 rpm using a mechanical stirrer.
[0038] Preferably, in S2, the ratio of aluminum hydroxide to diluent is 1:5 to 1:10 (mass ratio).
[0039] Preferably, the high temperature resistant epoxy modified silicone resin includes one or more of high temperature resistant epoxy modified silicone resin, siloxane modified epoxy resin, and silane modified epoxy resin; the ion capture agent includes one or more of ion exchange resin, chelating agent, ion selective resin, zeolite, and polymer adsorbent; the antioxidant includes one or more of antioxidant L1010, butylated hydroxytoluene, tetrakis (methylene (3,5-di-tert-butyl-4-hydroxyhydroxycinnamate)) methane, phenolic antioxidants, and thioester antioxidants; the curing agent includes curing agent 4,4'-diamino One or more of diphenylmethane, aromatic amine curing agent, anhydride curing agent, epoxy functional curing agent; the fluorine-containing resin includes one or more of fluorinated polymer, perfluoropolyether, fluorosilicone resin, fluorine-containing acrylic resin; the anhydride polymer material includes one or more of anhydride-modified polymer, maleic anhydride-modified resin, phthalic anhydride-modified polymer, nadimethyl anhydride-modified polymer; the matte powder includes one or more of matte agent, silica matte agent, wax-based matte agent, polymer matte agent; the diluent includes dimethylformamide (DMF).
[0040] The beneficial effects of the present invention are as follows:
[0041] The coating method provided by the present invention further reduces the Tg and dielectric constant of the polyimide layer by means of a secondary coating process and specific heat treatment and plasma treatment, and cooperates with the polyimide layer slurry provided by the present invention to greatly reduce the dielectric constant and Tg of the film. DETAILED DESCRIPTION
[0042] The technical scheme in the preparation examples of the present invention will be clearly and completely described below in conjunction with the preparation examples of the present invention. Obviously, the preparation examples described are only part of the preparation examples of the present invention, rather than all the preparation examples. Based on the preparation examples in the present invention, all other preparation examples obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0043] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0044] The experimental methods in the following preparation examples are conventional methods unless otherwise specified. The test materials used in the following preparation examples are purchased from commercial channels unless otherwise specified. The soluble polyimide liquid used in the following preparation examples and comparative preparation examples is Ube SP1, the high temperature resistant epoxy modified silicone resin is (high temperature resistant epoxy modified silicone resin) phenolic resin PMC-T383, the ion capture agent is IXE-100, the antioxidant is antioxidant L1010, the curing agent is Ube SP2, and the fluorine-containing resin is 500 (Kaina 500), the anhydride polymer material is maleic anhydride modified polyethylene E MB226D, matte powder is silica matte agent Ropaque TM Ultra E, diluent is dimethylformamide (DMF), silica is 200, graphene D50 = particle size below 0.1 um; PVA is Polyvinyl Alcohol (PVA), 99-100% Hydrolyzed, Reagent Grade, Sigma-Aldrich, product number 363170, and the polyimide film used is SKC black matte polyimide film.
[0045] Preparation Example 1 Preparation of opaque low dielectric low Tg polyimide layer slurry:
[0046] Formula: 120 parts of soluble polyimide liquid, 10 parts of high temperature resistant epoxy modified silicone resin, 0.3 parts of ion capture agent, 0.1 parts of antioxidant, 10 parts of curing agent, 10 parts of graphene, 15 parts of aluminum hydroxide, 10 parts of acid anhydride polymer material, 5 parts of diphenyl anhydride diamine, 5 parts of matte powder, diluent as needed, and 10 parts of silicon dioxide or zirconium oxide.
[0047] Preparation process:
[0048] S1, dissolving the fluorine-containing resin and the epoxy-modified silicone resin in a diluent to prepare solutions of the fluorine-containing resin and the epoxy-modified silicone resin, respectively, stirring and dissolving them, mixing the two resin solutions, and transferring them to a reaction kettle after ultrasonic treatment, and mechanically stirring;
[0049] S2, subjecting matte powder and aluminum hydroxide to ultrasonic dispersion in a diluent, and adding soluble polyimide liquid to premix;
[0050] S3, adding the mixture obtained in S1 and S2 into a reaction kettle in a required proportion, adding an ion capture agent, an antioxidant, graphene, anhydride polymer material, diphenyl anhydride diamine, a curing agent and silicon dioxide, and mixing to obtain a slurry.
[0051] The concentrations of the solutions of the fluorine-containing resin and the epoxy-modified silicone resin in S1 are controlled at 20 wt %.
[0052] Stir and dissolve as described in S1, and stir at room temperature for 3 h using a magnetic stirrer to ensure that the resin is completely dissolved.
[0053] The mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in the mixed solution of S1 is 10:10.
[0054] S1 described the use of ultrasonic treatment, ultrasonic power 200W, frequency 40kHz, treatment time 30min.
[0055] The mechanical stirring speed in S1 is 500 rpm, and the stirring time is 4 h at room temperature.
[0056] S2: ultrasonic dispersion, ultrasonic power 200W, frequency 40kHz, time 30min.
[0057] The mixture was pre-mixed as described in S2 and stirred at room temperature for 3 h using a magnetic stirrer.
[0058] In S2, aluminum hydroxide: diluent = 1:5 (mass ratio).
[0059] The mixture was stirred at 500 rpm using a mechanical stirrer at room temperature for 4 h.
[0060] Preparation Example 2 Preparation of opaque low dielectric low Tg polyimide layer slurry:
[0061] Formula: 120 parts of soluble polyimide liquid, 30 parts of high temperature resistant epoxy modified silicone resin, 0.5 parts of ion capture agent, 0.5 parts of antioxidant, 15 parts of curing agent, 15 parts of graphene, 25 parts of aluminum hydroxide, 35 parts of acid anhydride polymer material, 15 parts of diphenyl anhydride diamine, 15 parts of matte powder, diluent as needed, and 35 parts of silicon dioxide or zirconium oxide.
[0062] Preparation process:
[0063] S1, dissolving the fluorine-containing resin and the epoxy-modified silicone resin in a diluent to prepare solutions of the fluorine-containing resin and the epoxy-modified silicone resin, respectively, stirring and dissolving them, mixing the two resin solutions, and transferring them to a reaction kettle after ultrasonic treatment, and mechanically stirring;
[0064] S2, subjecting matte powder and aluminum hydroxide to ultrasonic dispersion in a diluent, and adding soluble polyimide liquid to premix;
[0065] S3, adding the mixture obtained in S1 and S2 into a reaction kettle in a required proportion, adding an ion capture agent, an antioxidant, graphene, anhydride polymer material, diphenyl anhydride diamine, a curing agent and silicon dioxide, and mixing to obtain a slurry.
[0066] The concentrations of the solutions of the fluorine-containing resin and the epoxy-modified silicone resin in S1 are controlled at 10 wt %.
[0067] Stir and dissolve as described in S1, and stir at room temperature for 2 h using a magnetic stirrer to ensure that the resin is completely dissolved.
[0068] The mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in the mixed solution of S1 is 10:10.
[0069] S1 described the use of ultrasonic treatment, ultrasonic power 100W, frequency 20kHz, treatment time 60min.
[0070] The mechanical stirring speed in S1 is 300 rpm, and the stirring time is 6 h at room temperature.
[0071] The ultrasonic dispersion described in S2 has an ultrasonic power of 100 W, a frequency of 20 kHz, and a time of 45 min.
[0072] The mixture was pre-mixed as described in S2 and stirred at room temperature for 2 h using a magnetic stirrer.
[0073] In S2, aluminum hydroxide: diluent = 1:10 (mass ratio).
[0074] The mixture was stirred at 300 rpm using a mechanical stirrer at room temperature for 5 h.
[0075] Preparation Example 3 Preparation of opaque low dielectric low Tg polyimide layer slurry:
[0076] Formula: 120 parts of soluble polyimide liquid, 20 parts of high temperature resistant epoxy modified silicone resin, 1 part of ion capture agent, 1 part of antioxidant, 15 parts of curing agent, 15 parts of graphene, 25 parts of aluminum hydroxide, 25 parts of acid anhydride polymer materials, 15 parts of diphenyl anhydride diamine, 15 parts of matte powder, diluent as needed, and 25 parts of silicon dioxide or zirconium oxide.
[0077] Preparation process:
[0078] S1, dissolving the fluorine-containing resin and the epoxy-modified silicone resin in a diluent to prepare solutions of the fluorine-containing resin and the epoxy-modified silicone resin, respectively, stirring and dissolving them, mixing the two resin solutions, and transferring them to a reaction kettle after ultrasonic treatment, and mechanically stirring;
[0079] S2, subjecting matte powder and aluminum hydroxide to ultrasonic dispersion in a diluent, and adding soluble polyimide liquid to premix;
[0080] S3, adding the mixture obtained in S1 and S2 into a reaction kettle in a required proportion, adding an ion capture agent, an antioxidant, graphene, anhydride polymer material, diphenyl anhydride diamine, a curing agent and silicon dioxide, and mixing to obtain a slurry.
[0081] The concentrations of the solutions of the fluorine-containing resin and the epoxy-modified silicone resin in S1 are controlled at 15 wt %.
[0082] Stir and dissolve as described in S1, and stir at room temperature for 3 h using a magnetic stirrer to ensure that the resin is completely dissolved.
[0083] The mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in the mixed solution of S1 is 10:10.
[0084] S1 described the use of ultrasonic treatment, ultrasonic power 150W, frequency 30kHz, treatment time 40min.
[0085] The mechanical stirring speed in S1 is 400 rpm, and the stirring time is 5 h at room temperature.
[0086] S2: ultrasonic dispersion, ultrasonic power 150W, frequency 30kHz, time 40min.
[0087] The mixture was pre-mixed as described in S2 and stirred at room temperature for 3 h using a magnetic stirrer.
[0088] In S2, aluminum hydroxide: diluent = 1:8 (mass ratio).
[0089] The mixture was stirred at 400 rpm using a mechanical stirrer at room temperature for 4 h.
[0090] Preparation Example 4 Preparation of opaque low dielectric low Tg polyimide layer slurry:
[0091] Formula: 120 parts of soluble polyimide liquid, 20 parts of high temperature resistant epoxy modified silicone resin, 1 part of ion capture agent, 1 part of antioxidant, 15 parts of curing agent, 15 parts of graphene, 25 parts of aluminum hydroxide, 25 parts of acid anhydride polymer materials, 15 parts of diphenyl anhydride diamine, 15 parts of matte powder, diluent as needed, and 25 parts of silicon dioxide or zirconium oxide.
[0092] Preparation process:
[0093] S1, dissolving the fluorine-containing resin and the epoxy-modified silicone resin in a diluent to prepare solutions of the fluorine-containing resin and the epoxy-modified silicone resin, respectively, stirring and dissolving them, mixing the two resin solutions, and transferring them to a reaction kettle after ultrasonic treatment, and mechanically stirring;
[0094] S2, subjecting matte powder and aluminum hydroxide to ultrasonic dispersion in a diluent, and adding soluble polyimide liquid to premix;
[0095] S3, adding the mixture obtained in S1 and S2 into a reaction kettle in a required proportion, adding an ion capture agent, an antioxidant, graphene, anhydride polymer material, diphenyl anhydride diamine, a curing agent and silicon dioxide, and mixing to obtain a slurry.
[0096] The concentrations of the solutions of the fluorine-containing resin and the epoxy-modified silicone resin in S1 are controlled at 15 wt %.
[0097] Stir and dissolve as described in S1, and stir at room temperature for 3 h using a magnetic stirrer to ensure that the resin is completely dissolved.
[0098] The mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in the mixed solution of S1 is 35:15.
[0099] S1 described the use of ultrasonic treatment, ultrasonic power 150W, frequency 30kHz, treatment time 40min.
[0100] The mechanical stirring speed in S1 is 400 rpm, and the stirring time is 5 h at room temperature.
[0101] S2: ultrasonic dispersion, ultrasonic power 150W, frequency 30kHz, time 40min.
[0102] The mixture was pre-mixed as described in S2 and stirred at room temperature for 3 h using a magnetic stirrer.
[0103] In S2, aluminum hydroxide: diluent = 1:8 (mass ratio).
[0104] The mixture was stirred at 400 rpm using a mechanical stirrer at room temperature for 4 h.
[0105] Preparation of polyimide layer slurry in comparative preparation example 1 (the difference from preparation example 4 is that S1 pretreatment and premixing are not performed):
[0106] Preparation of polyimide layer slurry:
[0107] Formula: 120 parts of soluble polyimide liquid, 20 parts of high temperature resistant epoxy modified silicone resin, 1 part of ion capture agent, 1 part of antioxidant, 15 parts of curing agent, 15 parts of graphene, 25 parts of aluminum hydroxide, 25 parts of acid anhydride polymer materials, 15 parts of diphenyl anhydride diamine, 15 parts of matte powder, diluent as needed, and 25 parts of silicon dioxide or zirconium oxide.
[0108] Preparation process:
[0109] S1, dissolving the fluorine-containing resin and the epoxy-modified silicone resin in a diluent to prepare solutions of the fluorine-containing resin and the epoxy-modified silicone resin, respectively, stirring and dissolving them, subjecting the two resin solutions to ultrasonic treatment, respectively, transferring them to a reaction kettle, and subjecting them to mechanical stirring;
[0110] S2, subjecting matte powder and aluminum hydroxide to ultrasonic dispersion in a diluent, and adding soluble polyimide liquid to premix;
[0111] S3, adding the mixture obtained in S1 and S2 into a reaction kettle in a required proportion, adding an ion capture agent, an antioxidant, graphene, anhydride polymer material, diphenyl anhydride diamine, a curing agent and silicon dioxide, and mixing to obtain a slurry.
[0112] The concentrations of the solutions of the fluorine-containing resin and the epoxy-modified silicone resin in S1 are controlled at 15 wt %.
[0113] Stir and dissolve as described in S1, and stir at room temperature for 3 h using a magnetic stirrer to ensure that the resin is completely dissolved.
[0114] The mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in S1 is 35:15.
[0115] S1 described the use of ultrasonic treatment, ultrasonic power 150W, frequency 30kHz, treatment time 40min.
[0116] The mechanical stirring speed in S1 is 400 rpm, and the stirring time is 5 h at room temperature.
[0117] S2: ultrasonic dispersion, ultrasonic power 150W, frequency 30kHz, time 40min.
[0118] The mixture was pre-mixed as described in S2 and stirred at room temperature for 3 h using a magnetic stirrer.
[0119] In S2, aluminum hydroxide: diluent = 1:8 (mass ratio).
[0120] The mixture was stirred at 400 rpm using a mechanical stirrer at room temperature for 4 h.
[0121] Preparation of polyimide layer slurry in comparative preparation example 2 (the difference from preparation example 4 is that S2 premixing is not performed):
[0122] Formula: 120 parts of soluble polyimide liquid, 20 parts of high temperature resistant epoxy modified silicone resin, 1 part of ion capture agent, 1 part of antioxidant, 15 parts of curing agent, 15 parts of graphene, 25 parts of aluminum hydroxide, 25 parts of acid anhydride polymer materials, 15 parts of diphenyl anhydride diamine, 15 parts of matte powder, diluent as needed, and 25 parts of silicon dioxide or zirconium oxide.
[0123] Preparation process:
[0124] S1, dissolving the fluorine-containing resin and the epoxy-modified silicone resin in a diluent to prepare solutions of the fluorine-containing resin and the epoxy-modified silicone resin, respectively, stirring and dissolving them, mixing the two resin solutions, and transferring them to a reaction kettle after ultrasonic treatment, and mechanically stirring;
[0125] S2, respectively taking matte powder, aluminum hydroxide, soluble polyimide liquid and diluent according to the amounts in Preparation Example 4, wherein the diluent is subjected to ultrasonic treatment according to this step in Preparation Example 4;
[0126] S3, adding the mixture or raw materials obtained in S1 and S2 into a reaction kettle in a required proportion, adding an ion capture agent, an antioxidant, graphene, anhydride polymer material, diphenyl anhydride diamine, a curing agent and silicon dioxide, and mixing to obtain a slurry.
[0127] The concentrations of the solutions of the fluorine-containing resin and the epoxy-modified silicone resin in S1 are controlled at 15 wt %.
[0128] Stir and dissolve as described in S1, and stir at room temperature for 3 h using a magnetic stirrer to ensure that the resin is completely dissolved.
[0129] The mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in the mixed solution of S1 is 35:15.
[0130] S1 described the use of ultrasonic treatment, ultrasonic power 150W, frequency 30kHz, treatment time 40min.
[0131] The mechanical stirring speed in S1 is 400 rpm, and the stirring time is 5 h at room temperature.
[0132] S2: ultrasound with an ultrasonic power of 150 W, a frequency of 30 kHz and a time of 40 min.
[0133] In S2, aluminum hydroxide: diluent = 1:8 (mass ratio).
[0134] The mixture was stirred at 400 rpm using a mechanical stirrer at room temperature for 4 h.
[0135] Preparation of polyimide layer slurry in comparative preparation example 3 (the difference from preparation example 4 is that matte powder is not premixed in S2 premix):
[0136] Formula: 120 parts of soluble polyimide liquid, 20 parts of high temperature resistant epoxy modified silicone resin, 1 part of ion capture agent, 1 part of antioxidant, 15 parts of curing agent, 15 parts of graphene, 25 parts of aluminum hydroxide, 25 parts of acid anhydride polymer materials, 15 parts of diphenyl anhydride diamine, 15 parts of matte powder, diluent as needed, and 25 parts of silicon dioxide or zirconium oxide.
[0137] Preparation process:
[0138] S1, dissolving the fluorine-containing resin and the epoxy-modified silicone resin in a diluent to prepare solutions of the fluorine-containing resin and the epoxy-modified silicone resin, respectively, stirring and dissolving them, mixing the two resin solutions, and transferring them to a reaction kettle after ultrasonic treatment, and mechanically stirring;
[0139] S2, subjecting aluminum hydroxide to ultrasonic dispersion treatment in a diluent, and adding a soluble polyimide solution for premixing;
[0140] S3, adding the mixture obtained in S1 and S2 into a reaction kettle in a required proportion, adding matte powder, ion capture agent, antioxidant, graphene, acid anhydride polymer material, diphenyl anhydride diamine, curing agent and silicon dioxide, and mixing to obtain slurry.
[0141] The concentrations of the solutions of the fluorine-containing resin and the epoxy-modified silicone resin in S1 are controlled at 15 wt %.
[0142] Stir and dissolve as described in S1, and stir at room temperature for 3 h using a magnetic stirrer to ensure that the resin is completely dissolved.
[0143] The mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in the mixed solution of S1 is 35:15.
[0144] S1 described the use of ultrasonic treatment, ultrasonic power 150W, frequency 30kHz, treatment time 40min.
[0145] The mechanical stirring speed in S1 is 400 rpm, and the stirring time is 5 h at room temperature.
[0146] S2: ultrasonic dispersion, ultrasonic power 150W, frequency 30kHz, time 40min.
[0147] The mixture was pre-mixed as described in S2 and stirred at room temperature for 3 h using a magnetic stirrer.
[0148] The amount of diluent used in S2 is the same as that in Preparation Example 4.
[0149] The mixture was stirred at 400 rpm using a mechanical stirrer at room temperature for 4 h.
[0150] Preparation of polyimide layer slurry in comparative preparation example 4 (the difference from preparation example 4 is that the premixing of aluminum hydroxide and soluble polyimide solution is not performed in S2 premixing):
[0151] Formula: 120 parts of soluble polyimide liquid, 20 parts of high temperature resistant epoxy modified silicone resin, 1 part of ion capture agent, 1 part of antioxidant, 15 parts of curing agent, 15 parts of graphene, 25 parts of aluminum hydroxide, 25 parts of acid anhydride polymer materials, 15 parts of diphenyl anhydride diamine, 15 parts of matte powder, diluent as needed, and 25 parts of silicon dioxide or zirconium oxide.
[0152] Preparation process:
[0153] S1, dissolving the fluorine-containing resin and the epoxy-modified silicone resin in a diluent to prepare solutions of the fluorine-containing resin and the epoxy-modified silicone resin, respectively, stirring and dissolving them, mixing the two resin solutions, and transferring them to a reaction kettle after ultrasonic treatment, and mechanically stirring;
[0154] S2, subjecting the matte powder to ultrasonic dispersion treatment in a diluent and premixing;
[0155] S3, adding the mixture obtained from S1 and S2 into a reaction kettle in a required proportion, adding aluminum hydroxide, soluble polyimide liquid, ion capture agent, antioxidant, graphene, acid anhydride polymer material, diphenyl anhydride diamine, curing agent and silicon dioxide, and mixing to obtain a slurry.
[0156] The concentrations of the solutions of the fluorine-containing resin and the epoxy-modified silicone resin in S1 are controlled at 15 wt %.
[0157] Stir and dissolve as described in S1, and stir at room temperature for 3 h using a magnetic stirrer to ensure that the resin is completely dissolved.
[0158] The mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in the mixed solution of S1 is 35:15.
[0159] S1 described the use of ultrasonic treatment, ultrasonic power 150W, frequency 30kHz, treatment time 40min.
[0160] The mechanical stirring speed in S1 is 400 rpm, and the stirring time is 5 h at room temperature.
[0161] S2: ultrasonic dispersion, ultrasonic power 150W, frequency 30kHz, time 40min.
[0162] The mixture was pre-mixed as described in S2 and stirred at room temperature for 3 h using a magnetic stirrer.
[0163] The amount of diluent used in S2 is the same as that in Preparation Example 4.
[0164] The mixture was stirred at 400 rpm using a mechanical stirrer at room temperature for 4 h.
[0165] Comparative Preparation Example 5 Preparation of polyimide layer slurry (the difference from Preparation Example 4 is that in the S2 premix, the matte powder is premixed separately, and the aluminum hydroxide and the soluble polyimide liquid are premixed separately):
[0166] Formula: 120 parts of soluble polyimide liquid, 20 parts of high temperature resistant epoxy modified silicone resin, 1 part of ion capture agent, 1 part of antioxidant, 15 parts of curing agent, 15 parts of graphene, 25 parts of aluminum hydroxide, 25 parts of acid anhydride polymer materials, 15 parts of diphenyl anhydride diamine, 15 parts of matte powder, diluent as needed, and 25 parts of silicon dioxide or zirconium oxide.
[0167] Preparation process:
[0168] S1, dissolving the fluorine-containing resin and the epoxy-modified silicone resin in a diluent to prepare solutions of the fluorine-containing resin and the epoxy-modified silicone resin, respectively, stirring and dissolving them, mixing the two resin solutions, and transferring them to a reaction kettle after ultrasonic treatment, and mechanically stirring;
[0169] S2, ultrasonically dispersing the matte powder in a diluent and premixing; ultrasonically dispersing the aluminum hydroxide in a diluent and adding a soluble polyimide solution and premixing;
[0170] S3, adding the mixture obtained in S1 and S2 into a reaction kettle in a required proportion, adding an ion capture agent, an antioxidant, graphene, anhydride polymer material, diphenyl anhydride diamine, a curing agent and silicon dioxide, and mixing to obtain a slurry
[0171] The concentrations of the solutions of the fluorine-containing resin and the epoxy-modified silicone resin in S1 are controlled at 15 wt %.
[0172] Stir and dissolve as described in S1, and stir at room temperature for 3 h using a magnetic stirrer to ensure that the resin is completely dissolved.
[0173] The mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in the mixed solution of S1 is 35:15.
[0174] S1 described the use of ultrasonic treatment, ultrasonic power 150W, frequency 30kHz, treatment time 40min.
[0175] The mechanical stirring speed in S1 is 400 rpm, and the stirring time is 5 h at room temperature.
[0176] S2: ultrasonic dispersion, ultrasonic power 150W, frequency 30kHz, time 40min.
[0177] The mixture was pre-mixed as described in S2 and stirred at room temperature for 3 h using a magnetic stirrer.
[0178] The total amount of diluent in S2 is the same as that in Preparation Example 4, wherein the matte powder is premixed with 50% of the diluent in S2.
[0179] The mixture was stirred at 400 rpm using a mechanical stirrer at room temperature for 4 h.
[0180] Preparation of polyimide layer slurry in comparative preparation example 6 (the difference from preparation example 4 is that S1 premixing and S2 premixing are not performed):
[0181] Formula: 120 parts of soluble polyimide liquid, 20 parts of high temperature resistant epoxy modified silicone resin, 1 part of ion capture agent, 1 part of antioxidant, 15 parts of curing agent, 15 parts of graphene, 25 parts of aluminum hydroxide, 25 parts of acid anhydride polymer materials, 15 parts of diphenyl anhydride diamine, 15 parts of matte powder, diluent as needed, and 25 parts of silicon dioxide or zirconium oxide.
[0182] Preparation process:
[0183] S1, dissolving the fluorine-containing resin and the epoxy-modified silicone resin in a diluent to prepare solutions of the fluorine-containing resin and the epoxy-modified silicone resin, respectively, stirring and dissolving them, subjecting the two resin solutions to ultrasonic treatment, respectively, transferring them to a reaction kettle, and subjecting them to mechanical stirring;
[0184] S2, respectively taking aluminum hydroxide, matte powder, soluble polyimide liquid and diluent according to the amounts in Preparation Example 4, wherein the diluent is subjected to ultrasonic treatment according to this step in Preparation Example 4;
[0185] S3, adding the mixture obtained in S1 and S2 into a reaction kettle in a required proportion, adding an ion capture agent, an antioxidant, graphene, anhydride polymer material, diphenyl anhydride diamine, a curing agent and silicon dioxide, and mixing to obtain a slurry.
[0186] The concentrations of the solutions of the fluorine-containing resin and the epoxy-modified silicone resin in S1 are controlled at 15 wt %.
[0187] Stir and dissolve as described in S1, and stir at room temperature for 3 h using a magnetic stirrer to ensure that the resin is completely dissolved.
[0188] The mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in S1 is 35:15.
[0189] S1 described the use of ultrasonic treatment, ultrasonic power 150W, frequency 30kHz, treatment time 40min.
[0190] The mechanical stirring speed in S1 is 400 rpm, and the stirring time is 5 h at room temperature.
[0191] S2: ultrasound with an ultrasonic power of 150 W, a frequency of 30 kHz and a time of 40 min.
[0192] In S2, aluminum hydroxide: diluent = 1:8 (mass ratio).
[0193] The mixture was stirred at 400 rpm using a mechanical stirrer at room temperature for 4 h.
[0194] Preparation of polyimide layer slurry in comparative preparation example 7 (the difference from preparation example 4 is that S1 premixing is not performed, and matte powder is not premixed in S2 premixing):
[0195] Formula: 120 parts of soluble polyimide liquid, 20 parts of high temperature resistant epoxy modified silicone resin, 1 part of ion capture agent, 1 part of antioxidant, 15 parts of curing agent, 15 parts of graphene, 25 parts of aluminum hydroxide, 25 parts of acid anhydride polymer materials, 15 parts of diphenyl anhydride diamine, 15 parts of matte powder, diluent as needed, and 25 parts of silicon dioxide or zirconium oxide.
[0196] Preparation process:
[0197] S1, dissolving the fluorine-containing resin and the epoxy-modified silicone resin in a diluent to prepare solutions of the fluorine-containing resin and the epoxy-modified silicone resin, respectively, stirring and dissolving them, subjecting the two resin solutions to ultrasonic treatment, respectively, transferring them to a reaction kettle, and subjecting them to mechanical stirring;
[0198] S2, subjecting aluminum hydroxide to ultrasonic dispersion treatment in a diluent, and adding a soluble polyimide solution for premixing;
[0199] S3, adding the mixture obtained in S1 and S2 into a reaction kettle in a required proportion, adding matte powder, ion capture agent, antioxidant, graphene, acid anhydride polymer material, diphenyl anhydride diamine, curing agent and silicon dioxide, and mixing to obtain slurry.
[0200] The concentrations of the solutions of the fluorine-containing resin and the epoxy-modified silicone resin in S1 are controlled at 15 wt %.
[0201] Stir and dissolve as described in S1, and stir at room temperature for 3 h using a magnetic stirrer to ensure that the resin is completely dissolved.
[0202] The mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in S1 is 35:15.
[0203] S1 described the use of ultrasonic treatment, ultrasonic power 150W, frequency 30kHz, treatment time 40min.
[0204] The mechanical stirring speed in S1 is 400 rpm, and the stirring time is 5 h at room temperature.
[0205] S2: ultrasonic dispersion, ultrasonic power 150W, frequency 30kHz, time 40min.
[0206] The mixture was pre-mixed as described in S2 and stirred at room temperature for 3 h using a magnetic stirrer.
[0207] The diluent in S3 is treated with ultrasound with an ultrasound power of 150 W, a frequency of 30 kHz, and a treatment time of 40 min.
[0208] The amount of diluent used in S2 is the same as that in Preparation Example 4.
[0209] The mixture was stirred at 400 rpm using a mechanical stirrer at room temperature for 4 h.
[0210] Preparation of polyimide layer slurry in comparative preparation example 8 (the difference from preparation example 4 is that S1 premixing is not performed, and matte powder is not premixed in S2 premixing):
[0211] Formula: 120 parts of soluble polyimide liquid, 20 parts of high temperature resistant epoxy modified silicone resin, 1 part of ion capture agent, 1 part of antioxidant, 15 parts of curing agent, 15 parts of graphene, 25 parts of aluminum hydroxide, 25 parts of acid anhydride polymer materials, 15 parts of diphenyl anhydride diamine, 15 parts of matte powder, diluent as needed, and 25 parts of silicon dioxide or zirconium oxide.
[0212] Preparation process:
[0213] S1, dissolving the fluorine-containing resin and the epoxy-modified silicone resin in a diluent to prepare solutions of the fluorine-containing resin and the epoxy-modified silicone resin, respectively, stirring and dissolving them, subjecting the two resin solutions to ultrasonic treatment, respectively, transferring them to a reaction kettle, and subjecting them to mechanical stirring;
[0214] S2, subjecting the matte powder to ultrasonic dispersion treatment in a diluent and premixing;
[0215] S3, adding the mixture obtained from S1 and S2 into a reaction kettle in a desired proportion, adding aluminum hydroxide, soluble polyimide liquid, ion capture agent, antioxidant, graphene, acid anhydride polymer material, diphenyl anhydride diamine, curing agent and silicon dioxide, and mixing to obtain a slurry
[0216] The concentrations of the solutions of the fluorine-containing resin and the epoxy-modified silicone resin in S1 are controlled at 15 wt %.
[0217] Stir and dissolve as described in S1, and stir at room temperature for 3 h using a magnetic stirrer to ensure that the resin is completely dissolved.
[0218] The mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in S1 is 35:15.
[0219] S1 described the use of ultrasonic treatment, ultrasonic power 150W, frequency 30kHz, treatment time 40min.
[0220] The mechanical stirring speed in S1 is 400 rpm, and the stirring time is 5 h at room temperature.
[0221] S2: ultrasonic dispersion, ultrasonic power 150W, frequency 30kHz, time 40min.
[0222] The mixture was pre-mixed as described in S2 and stirred at room temperature for 3 h using a magnetic stirrer.
[0223] The amount of diluent used in S2 is the same as that in Preparation Example 4.
[0224] The mixture was stirred at 400 rpm using a mechanical stirrer at room temperature for 4 h.
[0225] Preparation of polyimide layer slurry in comparative preparation example 9 (the difference from preparation example 4 is that S1 premixing is not performed, and in S2 premixing, matte powder is premixed separately, and aluminum hydroxide and soluble polyimide liquid are premixed separately):
[0226] Formula: 120 parts of soluble polyimide liquid, 20 parts of high temperature resistant epoxy modified silicone resin, 1 part of ion capture agent, 1 part of antioxidant, 15 parts of curing agent, 15 parts of graphene, 25 parts of aluminum hydroxide, 25 parts of acid anhydride polymer materials, 15 parts of diphenyl anhydride diamine, 15 parts of matte powder, diluent as needed, and 25 parts of silicon dioxide or zirconium oxide.
[0227] Preparation process:
[0228] S1, dissolving the fluorine-containing resin and the epoxy-modified silicone resin in a diluent to prepare solutions of the fluorine-containing resin and the epoxy-modified silicone resin, respectively, stirring and dissolving them, subjecting the two resin solutions to ultrasonic treatment, respectively, transferring them to a reaction kettle, and subjecting them to mechanical stirring;
[0229] S2, ultrasonically dispersing the matte powder in a diluent and premixing; ultrasonically dispersing the aluminum hydroxide in a diluent and adding a soluble polyimide solution and premixing;
[0230] S3, adding the mixture obtained in S1 and S2 into a reaction kettle in a required proportion, adding an ion capture agent, an antioxidant, graphene, anhydride polymer material, diphenyl anhydride diamine, a curing agent and silicon dioxide, and mixing to obtain a slurry.
[0231] The concentrations of the solutions of the fluorine-containing resin and the epoxy-modified silicone resin in S1 are controlled at 15 wt %.
[0232] Stir and dissolve as described in S1, and stir at room temperature for 3 h using a magnetic stirrer to ensure that the resin is completely dissolved.
[0233] The mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in S1 is 35:15.
[0234] S1 described the use of ultrasonic treatment, ultrasonic power 150W, frequency 30kHz, treatment time 40min.
[0235] The mechanical stirring speed in S1 is 400 rpm, and the stirring time is 5 h at room temperature.
[0236] S2: ultrasonic dispersion, ultrasonic power 150W, frequency 30kHz, time 40min.
[0237] The mixture was pre-mixed as described in S2 and stirred at room temperature for 3 h using a magnetic stirrer.
[0238] In S2, aluminum hydroxide: diluent = 1:8 (mass ratio).
[0239] The mixture was stirred at 400 rpm using a mechanical stirrer at room temperature for 4 h.
[0240] Preparation of polyimide layer slurry in comparative preparation example 10 (the difference from comparative preparation example 4 is that all raw materials are directly mixed):
[0241] Formula: 120 parts of soluble polyimide liquid, 20 parts of high temperature resistant epoxy modified silicone resin, 1 part of ion capture agent, 1 part of antioxidant, 15 parts of curing agent, 15 parts of graphene, 25 parts of aluminum hydroxide, 25 parts of acid anhydride polymer material, 15 parts of diphenyl anhydride diamine, 15 parts of matte powder, diluent as needed, and 25 parts of silicon dioxide or zirconium oxide. The mass ratio of fluorine-containing resin to epoxy modified silicone resin is 35:15.
[0242] Preparation process:
[0243] The total amount of diluent was added according to the amount in Preparation Example 4, all the components in the above formula were mixed, and dispersed for 2 hours in a high-speed disperser at a speed of 800 rpm. To avoid excessive temperature during the dispersion process, a constant temperature water tank was added to maintain the temperature at 30°C to prepare a slurry.
[0244] Comparative Preparation Example 11 Preparation of polyimide layer slurry:
[0245] The difference from Preparation Example 4 is that the mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in S1 is 40:50.
[0246] Comparative Preparation Example 12 Preparation of polyimide layer slurry:
[0247] The difference from Preparation Example 4 is that the mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in S1 is 45:50.
[0248] Comparative Preparation Example 13 Preparation of polyimide layer slurry:
[0249] The difference from Preparation Example 4 is that the mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in S1 is 65:30.
[0250] Comparative Preparation Example 14 Preparation of polyimide layer slurry:
[0251] The difference from Preparation Example 4 is that the mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in S1 is 60:30.
[0252] Comparative Preparation Example 15 Preparation of polyimide layer slurry:
[0253] The difference from Preparation Example 4 is that the mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in S1 is 50:30.
[0254] Comparative Preparation Example 16 Preparation of polyimide layer slurry:
[0255] The difference from Preparation Example 4 is that the mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in S1 is 40:30.
[0256] Comparative Preparation Example 17 Preparation of polyimide layer slurry:
[0257] The difference from Preparation Example 4 is that the mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in S1 is 35:30.
[0258] Comparative Preparation Example 18 Preparation of polyimide layer slurry:
[0259] The difference from Preparation Example 4 is that the mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in S1 is 75:30.
[0260] Comparative Preparation Example 19 Preparation of polyimide layer slurry:
[0261] The difference from Preparation Example 4 is that the mass ratio of the fluorine-containing resin to the epoxy-modified silicone resin in S1 is 80:30.
[0262] Comparative Preparation Example 20 Preparation of polyimide layer slurry:
[0263] The difference from Comparative Preparation Example 10 is that the formula does not include fluorine-containing resin.
[0264] Comparative Preparation Example 21 Preparation of polyimide layer slurry:
[0265] The difference from Comparative Preparation Example 10 is that aluminum hydroxide is not included in the formula.
[0266] Comparative Preparation Example 22 Preparation of polyimide layer slurry:
[0267] The difference from Comparative Preparation Example 10 is that silicon dioxide is not included in the formula.
[0268] Comparative Preparation Example 23 Preparation of polyimide layer slurry:
[0269] The difference from Comparative Preparation Example 10 is that the formula does not include anhydride polymer materials.
[0270] Example 1-27 Coating process for preparing opaque low dielectric low Tg polyimide film:
[0271] (1) spraying the polyimide layer slurries obtained in Preparation Examples 1-4 and Comparative Preparation Examples 1-23 onto the surface of the polyimide film, respectively, and pre-drying;
[0272] (2) adding PVA to the corresponding polyimide layer slurry, stirring evenly and spraying it on the surface of the pre-dried coating for secondary pre-drying;
[0273] (3) heat treating the obtained film;
[0274] (4) The surface of the heat-treated film is subjected to plasma treatment to obtain an opaque, low-dielectric, low-Tg polyimide film.
[0275] The pre-drying in step (1) includes pre-drying at 90° C. for 30 minutes.
[0276] The film thickness obtained by spraying in step (1) is 50% of the total spraying thickness.
[0277] The amount of PVA added in step (2) is 3wt% of the slurry.
[0278] The secondary pre-drying in step (2) includes pre-drying at 80° C. for 30 minutes.
[0279] The total thickness of the film obtained by spraying in steps (1) and (2) is 25 μm.
[0280] The heat treatment in step (3) includes a first heat treatment and a second heat treatment, wherein the first heat treatment includes: heating to 150°C at 10°C / min and maintaining for 1.5h.
[0281] The heat treatment in step (3), wherein the second heat treatment comprises: continuing to increase the temperature to 300°C at 20°C / min and maintaining for 2.5 hours.
[0282] The plasma treatment in step (4) uses an oxygen plasma device with a power setting of 90 W, an oxygen flow rate of 80 sccm, and a time of 30 min.
[0283] Example 28 Coating process for preparing opaque low dielectric low Tg polyimide film:
[0284] (1) spraying the polyimide layer slurry obtained in Preparation Example 1 onto the surface of the polyimide film and pre-drying it;
[0285] (2) adding PVA to the polyimide layer slurry, stirring evenly and spraying it on the surface of the pre-dried coating for secondary pre-drying;
[0286] (3) heat treating the obtained film;
[0287] (4) The surface of the heat-treated film is subjected to plasma treatment to obtain an opaque, low-dielectric, low-Tg polyimide film.
[0288] The pre-drying in step (1) includes pre-drying at 95° C. for 40 minutes.
[0289] The film thickness obtained by spraying in step (1) is 40% of the total spraying thickness.
[0290] The amount of PVA added in step (2) is 5wt% of the slurry.
[0291] The secondary pre-drying in step (2) includes pre-drying at 85° C. for 30 minutes.
[0292] The total thickness of the film obtained by spraying in steps (1) and (2) is 25 μm.
[0293] The heat treatment in step (3) includes a first heat treatment and a second heat treatment, wherein the first heat treatment includes: heating to 180°C at 15°C / min and maintaining for 1 hour.
[0294] The heat treatment in step (3), wherein the second heat treatment comprises: continuing to increase the temperature to 330°C at 30°C / min and maintaining for 2h.
[0295] The plasma treatment in step (4) uses oxygen plasma equipment with a power setting of 100 W, an oxygen flow rate of 100 sccm, and a time of 20 min.
[0296] Comparative Examples 1-27:
[0297] The difference from Example 1-27 is that the slurries prepared in Preparation Example 1-4 and Comparative Preparation Example 1-23 are directly taken in sequence to perform the following operations:
[0298] The obtained slurry is coated on the surface of the polyimide film, and after curing, an opaque low-dielectric low-Tg polyimide film is obtained. The coating method includes spin coating; the curing method includes standing at room temperature for 12 hours, gradually heating to 60°C and maintaining for 2 hours, and further heating to 120°C and maintaining for 2 hours. The coating thickness is 25 μm.
[0299] The difference between Comparative Example 28 and Example 1 is that PVA is not added.
[0300] The difference between Comparative Example 29 and Example 1 is that no secondary coating is performed, and a coating with a thickness of 25 μm is prepared, and the slurry used is the slurry of step (1).
[0301] The difference between Comparative Example 30 and Example 1 is that no secondary coating is performed, and a coating with a thickness of 25 μm is prepared. The slurry uses the slurry to which PVA is added in step (2).
[0302] The difference between Comparative Example 31 and Example 1 is that no secondary coating is performed, only one coating is performed to prepare a coating with a thickness of 25 μm, the slurry uses the slurry with PVA added in step (2), and no plasma treatment is performed.
[0303] Performance testing:
[0304] The samples obtained in Example 1 (prepared with 25 μm thickness and 38 μm thickness, respectively) were taken for sample testing, and the results are shown in Table 1.
[0305] Table 1 Example 1 Routine testing of samples
[0306]
[0307]
[0308] The transmittance, dielectric constant and TG of the films obtained in all the above examples and comparative examples were tested. The results are shown in Table 2.
[0309] Table 2 Test results (Another invention developed by the company at the same time, "An opaque low-dielectric low-Tg polyimide film and its preparation method", was tested at the same time, and the horizontal comparison experimental data is the same batch of experimental data conducted on the same batch of experimental samples)
[0310]
[0311]
[0312] It can be seen from the above results that the coating method provided by the present invention can effectively reduce the dielectric constant and Tg of the film product, including the secondary coating and the PVA added in the surface layer and the plasma treatment are crucial to the obtained effect. In addition, the formula provided by the present invention can provide lower transmittance, dielectric constant and TG; the blending of fluorine-containing resin and epoxy resin in the formula has an insignificant contribution to the reduction of the above three groups of parameters; when aluminum hydroxide, polyimide and matte powder are premixed at the same time, it has a very significant contribution to the reduction of the above three groups of parameters, but this phenomenon is not seen when aluminum hydroxide and polyimide are pretreated alone or matte powder and diluent are pretreated alone. In the work of other researchers, we know that the dielectric constant of the product can be controlled to a certain extent by pre-blending fluorine-containing resin with epoxy-modified silicone resin, but this effect does not show a significant effect in the work of the present invention; in addition, we know that aluminum hydroxide, polyimide or matte powder are pre-mixed with diluents respectively, which may improve the uniformity of mixing, improve the dispersibility of components or the compatibility between components, but in the work of the present invention, the pre-mixing alone does not seem to work. Therefore, it can be seen that the pre-mixing of aluminum hydroxide, polyimide or matte powder with diluents affects the dielectric constant and TG of the final film, and its principle is not to affect dispersibility or compatibility. At the same time, when the four components are blended, the effect of adding on the dielectric constant and GT becomes more significant. When aluminum hydroxide, polyimide and matte powder are pre-mixed at the same time, a closer interface interaction is formed between these components, and aluminum hydroxide particles will form more interfaces in the polyimide matrix, thereby increasing the interface density of the material, resulting in a decrease in the dielectric constant and TG. This enhanced interface interaction may not be obvious when pre-mixed alone. The addition of aluminum hydroxide and matte powder may change the formation process of the polyimide network structure. Through premixing, these inorganic fillers may form a more uniform distribution in the polyimide matrix, inhibiting the formation of high-density cross-linked structures, thereby reducing TG and dielectric constant. Premixing may change the surface chemical properties of aluminum hydroxide, polyimide and matte powder, making them more likely to participate in chemical reactions during the subsequent curing process. The functional groups on the surface of aluminum hydroxide and matte powder may react with the polyimide matrix to form new chemical bonds, thereby affecting the dielectric constant and TG of the film. When the mass ratio of fluorine-containing resin to epoxy-modified silicone resin is 35:15 or 1:1, the film has the lowest dielectric constant and the lowest TG.If the mass ratio of the two is greater than 35:15, less than 1:1, or between 35:15 and 1:1, the dielectric constant of the film increases, while TG does not change much. The possible reasons are: when the mass ratio is 35:15 or 1:1, the fluorine-containing resin and the epoxy-modified silicone resin may form the best interaction and interface compatibility at the molecular level, forming a uniform microphase separation structure, or providing the best freedom of movement of polymer chain segments. When the mass ratio deviates from this range, the above-mentioned optimal balance is destroyed, so the dielectric constant changes significantly, but because the cross-linking density of the overall structure does not change much, the TG does not change significantly.
[0313] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
[0314] The present invention and its implementation methods are described above, and such description is not restrictive, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can design methods and embodiments similar to the technical solution without creativity, which should all fall within the protection scope of the present invention.
Claims
1. A coating process for preparing a light-impermeable low-dielectric low-Tg polyimide film, characterized in that: The following steps are involved: (1) spraying the polyimide layer slurry on the surface of the polyimide film and pre-drying it; (2) adding PVA to the polyimide layer slurry, stirring evenly and spraying it on the surface of the pre-dried coating for secondary pre-drying; (3) heat treating the obtained film; (4) The surface of the heat-treated film is subjected to plasma treatment to obtain an opaque, low-dielectric, low-Tg polyimide film.
2. The coating process for preparing the light-proof low-dielectric low-Tg polyimide film according to claim 1, characterized in that: The pre-drying in step (1) comprises pre-drying at 90-95° C. for 30-40 minutes.
3. The coating process for preparing the light-proof low-dielectric low-Tg polyimide film according to claim 1, characterized in that: The film thickness obtained by spraying in step (1) is 30-50% of the total spraying thickness.
4. The coating process for preparing the light-proof low-dielectric low-Tg polyimide film according to claim 1, characterized in that: The amount of PVA added in step (2) is 3-5wt% of the slurry.
5. The coating process for preparing the light-proof low-dielectric low-Tg polyimide film according to claim 1, characterized in that: The secondary pre-drying in step (2) comprises pre-drying at 80-85° C. for 30-40 minutes.
6. The coating process for preparing the light-proof low-dielectric low-Tg polyimide film according to claim 1, characterized in that: The total thickness of the film obtained by spraying in steps (1) and (2) is 20-50 μm.
7. The coating process for preparing the light-proof low-dielectric low-Tg polyimide film according to claim 1, characterized in that: The heat treatment in step (3) includes a first heat treatment and a second heat treatment, wherein the first heat treatment includes: heating to 150-180°C at 10-15°C / min and maintaining for 1-1.5h.
8. The coating process for preparing the light-proof low-dielectric low-Tg polyimide film according to claim 7, characterized in that: The heat treatment in step (3), wherein the second heat treatment comprises: continuing to increase the temperature to 300-330°C at 20-30°C / min and maintaining for 2-2.5h.
9. The coating process for preparing the light-proof low-dielectric low-Tg polyimide film according to claim 1, characterized in that: The plasma treatment in step (4) uses oxygen plasma equipment with a power setting of 90-100 W, an oxygen flow rate of 80-100 sccm, and a time of 20-30 min.
10. The coating process for preparing the light-proof low-dielectric low-Tg polyimide film according to claim 1, characterized in that: The components in the polyimide layer slurry include, by mass, 30-120 parts of soluble polyimide liquid, 10-35 parts of high temperature resistant epoxy modified silicone resin, 0.3-1 parts of ion capture agent, 0.1-1 parts of antioxidant, 10-15 parts of curing agent, 10-15 parts of graphene, 15-35 parts of aluminum hydroxide, 10-35 parts of fluorine-containing resin, 10-35 parts of acid anhydride polymer material, 5-15 parts of diphenyl anhydride diamine, 5-15 parts of matte powder, and diluent as needed, and also includes 10-35 parts of silicon dioxide or zirconium oxide.